IDEOLOGICAL THREATS TO SECURITY AND STABILITY UNDER GLOBALIZATION (Scientific journal of the Fergana State University, 2023)
This article, on the one hand, shows the advantages of the globalization process in Uzbekistan at the present time, including equipping all sectors of the economy with modern equipment and technologies, widespread attraction of investments, rational use of the development path and its uniqueness.